AKTUALISASI PENGEMBANGAN SUMBERDAYA MANUSIA DI LINGKUNGAN KERJA - RACHMAWATY, AYU; IRIANI YUDANINGRUM, BUDI (STIEKOP MALANG PRESS, 2025)
Purpose – The actualization of human resource development (HRD) within the workplace is paramount for fostering organizational growth and enhancing employee capabilities. Strategic implementation of HRD initiatives ensures a skilled and adaptable workforce, capable of meeting evolving industry demands and contributing to sustained competitive advantage. Consequently, prioritizing and effectively executing HRD programs is essential for long-term organizational success. Design/methodology/approach – This study employs an action research methodology to analyze the actualization of human resource development within the workplace. Data collection involves participatory observation and focused interviews with employees and management. The analysis focuses on identifying existing barriers to development and collaboratively implementing interventions to foster a more supportive and effective learning environment. Findings – The study's findings illuminate the critical role of human resource development actualization within the workplace. Specifically, observed impacts include enhanced employee skills, increased job satisfaction, and improved overall organizational performance. These results suggest a strong positive correlation between strategic human resource development initiatives and tangible benefits for both employees and the organization. Research limitations/implications – Research on the actualization of human resource development in the workplace, while contributing valuable insights, is constrained by its specific context and limited sample size. Consequently, the generalizability of findings to diverse organizational settings and broader populations requires cautious interpretation. Future research should explore these dynamics across varied industries and utilize more expansive datasets to strengthen the external validity of the results. Originality/value – The actualization of human resource development within the workplace hinges on fostering originality and demonstrable value creation. Traditional models often prioritize standardized skill sets, neglecting the potential for novel approaches and individual initiative. To remain competitive, organizations must cultivate environments that encourage innovative problem-solving and allow employees to contribute unique perspectives, ultimately leading to enhanced productivity and sustainable growth.